Bank Efficiency in Indonesia: An Analysis through Data Envelopment Analysis (DEA) Approach - Alia Gantina Shiti Mariam; Try Pena Purba; Fajra Octrina (Dinasti Publisher, 2025)
The purpose of this study is to see the efficiency level of banks, and to see which units need to be increased or decreased. This study will look at the efficiency value of government-owned banks from 2017 to 2022 using the Data Envelopment Analysis (DEA) approach. The research findings show that only one bank is consistently efficient during the study period, while other banks need to further improve input utilization to produce optimal output. The existing literature has not discussed much about the in-depth discussion of technical and scale efficiency and how additional changes and adjustments are needed to reach the efficiency limit.